Experimental Infection of Domestic Pigs with African Swine Fever Virus Lithuania 2014 Genotype II Field Isolate. Issue 1 (22nd March 2015) - Gallardo, C.; Soler, A.; Nieto, R.; Cano, C.; Pelayo, V.; Sánchez, M. A.; Pridotkas, G.; Fernandez‐Pinero, J.; Briones, V.; Arias, M.
Summary: An experimental infection was conducted to evaluate horizontal transmission, clinical, virological and humoral response induced in domestic pigs infected with African swine fever (ASF) genotype II virus circulating in 2014 into the European Union (EU). Ten naive pigs were placed in contact with eight pigs experimentally inoculated with the Lithuanian LT14/1490 ASF virus (ASFV) responsible for the first ASF case detected in wild boar in Lithuania in January 2014. Clinical examination and rectal temperature were recorded each day. Blood sampling from every animal was carried out twice weekly. Blood samples were examined for presence of ASF virus‐specific antibodies and for determining the ASFV viral load. From the obtained results, it was concluded that the Lithuanian ASFV induced an acute disease which resulted in 94, 5% mortality. The disease was easily detected by real‐time PCR prior to the onset of clinical signs and 33% of the animals seroconverted. All findings were in accordance with observations previously made in domestic pigs and wild boar when infected with ASF genotype II viruses characterized by a high virulence. One in‐contact pig remained asymptomatic and survived the infection. The role of such animals in virus transmission would need further investigation.